Optimization of Motor Vehicle Ownership Books Publishing to Improve the Quality of Public Services Towards Polri Precision in the Jurisdiction of The Police of Pekalongan City - Raihan Argya (Indonesian Journal of Police Studies, 2022)
The Precision Police was present as a concept that was promoted during the leadership of Police General Listyo Sigit Prabowo as the National Police Chief. One of the areas of transformation that is targeted in this concept is in the field of public services. One form of public service activity is the issuance of BPKB which is the main problem discussed in the writing of this final project. So that this final project was made with the intention of being able to get an overview of the issuance of BPKB carried out by the Pekalongan City Police with 2 main objectives following it, namely to be able to know service standards and the mechanism for issuing BPKB. In describing the various problems that exist, several library sources are used as a means to carry out an analysis consisting of research literature in the form of previous thesis writing and conceptual literature consisting of management theory regarding management functions and elements as well as several concepts regarding Regident Ranmor, Public Service and Police Precision. The research method is an inseparable part of a thesis writing so that in this final project the research methods used include a qualitative research approach with descriptive research type. Furthermore, the research location as mentioned above is the Pekalongan City Police Station. Then, in obtaining various data, the data collection techniques used were interviews, observations and document review. In the research conducted, it was found that the issuance of BPKB still needs to be improved in terms of the problem of the incompatibility of the preparation of service standards based on Law Number 25 of 2009 concerning Public Services and the implementation of the Precision Police concept in the BPKB issuance mechanism has not been maximized.